Pelaksanaan Jaminan Hak Keperdataan Subyek Hukum Manusia Atas Perubahan Atau Penambahan Nama Dalam Hukum Positif Indonesia Di Serang Banten - Dede Agus; Lia Riesta Dewi (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
In accordance with the right to naming the rights of each subject human law, the change or  addition of names are also the same. Therefore, this research aims to describe how the guarantee and implementation of civil rights for the change or addition of names in positive law and the legal consequences for population documents and other legal documents. This research method, normative juridical based on secondary data and much supported primary data, and finally were analysed qualitative descriptive. The research result shows that the change or addition of names in population documents and civil registries has been guaranteed implicitly and explicitly by the Law No. 23 of 2006 on Population Administration and Law No.24 of 2013 on the amendments law, and it implementation regulations. Likewise, the implementation of civil rights for changes or additions to names in population documents and civil registries, as well as other documents has been in practice. Due to law arising, such as: must obtain a district court decisions, a request for a changes to the population and civil registries, margin notes on the deed register, change the  name of other population identity on a documents, as well as sanctions had been imposed on population administration in according to the population administration Law.